2015
DOI: 10.1007/s00266-015-0555-z
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Postoperative Complications of Tissue Expander/Implant Breast Reconstruction Using Acellular Dermal Matrix

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…29 However, our study suggests that there is no difference in complications between the 2 groups; however, our sample size is relatively small, and definitive conclusions cannot be made. In theory, autologous tissue should be less immunogenic and more compatible, suggesting perhaps that there should be a lower complication especially with regard to infection rates.…”
Section: Discussionmentioning
confidence: 59%
“…29 However, our study suggests that there is no difference in complications between the 2 groups; however, our sample size is relatively small, and definitive conclusions cannot be made. In theory, autologous tissue should be less immunogenic and more compatible, suggesting perhaps that there should be a lower complication especially with regard to infection rates.…”
Section: Discussionmentioning
confidence: 59%
“…They found that incorporation of ADMs increased the incidence of overall complications (odds ratio [OR]: 1.33 compared with control), hematoma/seroma formation (OR: 1.66), and infection (OR: 1.47). 40 Exact rate of seroma formation following ADM use was then quantified in 2010, with rates of 14.1 versus 2.7% reported when comparing ADM to non-ADM breast reconstruction, respectively. 26 Similarly, the same study showed the rates of infection after ADM use to be 8.9 versus 2.1% for those patients who did not receive ADM. 26 However, in 2011, a separate retrospective review of 331 patients reported only a 1.5% seroma rate and a 3.0% infection rate following immediate single-stage implant reconstructions with ADM. 41 An additional 2011 study of 470 total patients reported a 6.9% overall wound infection rate in the ADM cohort compared with 2.5% in the non-ADM cohort, but the difference was not statistically significant.…”
Section: Disadvantages Of Acellular Dermal Matrix Usementioning
confidence: 99%
“…The risk of complications, including SSI, is affected by the type of breast surgery and whether breast reconstruction is performed. Current surgical options include breast-saving techniques, mastectomy, autograft techniques, use of an acellular dermal matrix, implantation of breast implants, and a combination of these methods [4,[5][6][7]. SSI occurs in an average of 2-7% of patients who undergo breast surgery.…”
Section: Discussionmentioning
confidence: 99%